The effect of the Sarbanes-Oxley Act on CEO pay for luck - Teodora Paligorova (Bank of Canada, 2008)
According to the rent-extraction hypothesis, weak corporate governance allows entrenched CEOs to capture the pay-setting process and benefit from events outside of their controlget paid for luck. In this paper, I find that the independence requirement imposed on boards of directors by the Sarbanes-Oxley Act of 2002 (SOX), together with the governance regulations subsequently introduced by stock exchanges, affects CEO pay structure. In firms whose corporate boards were originally less independent, and thus more affected by these provisions, CEO pay for performance strengthened while pay for luck decreased after adopting SOX. In contrast, those firms that exhibited strong board independence prior to SOX showed little evidence of pay for luck and little change in pay for performance following the adoption of SOX. The results are consistent with the rent-extraction hypothesis, and they are robust to alternative explanations such as asymmetric benchmarks, oligopoly, and managerial talent.
Keywords: G38; J33; M52; 330; Labour markets; Führungskräfte; Vergütungssystem; Leistungsentgelt; Corporate Governance; Internes Kontrollsystem; USA